2012
DOI: 10.1177/0091270011426875
|View full text |Cite
|
Sign up to set email alerts
|

No Pharmacokinetic Interaction Between Lacosamide and Valproic Acid in Healthy Volunteers

Abstract: Two open-label, randomized, multiple-dose clinical studies evaluated the potential for pharmacokinetic interaction between the antiepileptic drugs lacosamide and valproic acid. The influence of lacosamide on valproic acid pharmacokinetics (trial A) and valproic acid on lacosamide pharmacokinetics (trial B) was investigated in 32 healthy male volunteers, 16 in each trial. Volunteers in trial A received valproic acid (300 mg bid) with randomization to either early or late addition of lacosamide (200 mg bid). Tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 16 publications
(28 reference statements)
3
19
0
1
Order By: Relevance
“…Warfarin was administered on the third day of lacosamide intake; the AUCs of R‐ and S‐warfarin were essentially unchanged relatively to the warfarin alone period and even 3% lower for S‐warfarin, suggesting no evidence of enzyme induction. Given that lacosamide is not known to be an enzyme‐inducing or inhibiting AED (Bialer et al., ; Cawello et al., , ; UCB, ,b; Cawello & Bonn, ), the results summarized here are consistent with its known properties.…”
Section: Discussionsupporting
confidence: 82%
“…Warfarin was administered on the third day of lacosamide intake; the AUCs of R‐ and S‐warfarin were essentially unchanged relatively to the warfarin alone period and even 3% lower for S‐warfarin, suggesting no evidence of enzyme induction. Given that lacosamide is not known to be an enzyme‐inducing or inhibiting AED (Bialer et al., ; Cawello et al., , ; UCB, ,b; Cawello & Bonn, ), the results summarized here are consistent with its known properties.…”
Section: Discussionsupporting
confidence: 82%
“…Lacosamide plasma concentrations were determined using a standard method (17). Summary statistics were calculated separately for each of the three POS studies.…”
Section: Pharmacokinetic Assessmentmentioning
confidence: 99%
“…On the other hand, the effect of VPA, a broad-spectrum enzyme inhibitor, 16 on LCM metabolism was assessed in a specific trial conducted in 16 healthy volunteers receiving VPA, 300 mg bid, combined with LCM, 200 mg twice daily for 22 days, but no significant effect was detected. 9 This trial was chosen in an attempt to limit overall exposure and minimize drug adverse effects in healthy volunteers, and these results may not be transferable to patients with epilepsy, who are generally treated with higher doses of VPA. From the preliminary analysis of the subgroup of patients not on AED strong inducers in the present work, L/D values of LCM in patients comedicated with VPA alone were similar to those receiving drugs that were not strong enzyme inducers/inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…3 The extent of protein binding is controversial, with initial reports of 15%, 6 whereas a recent study in patients with epilepsy showed a substantial (approximately 90%) LCM protein binding. 7 The pharmacokinetic interaction potential of LCM is reported to be low, 6 and no drug-drug interaction has been detected between LCM and both potent enzyme inducers, such as carbamazepine (CBZ), 8 and broad-spectrum inhibitors of drug-metabolizing enzymes, such as valproic acid (VPA), 9 in specific trials conducted in healthy subjects. However, analysis of clinical trials in patients with epilepsy indicated a 25% decrease of LCM when patients received concomitant hepatic enzyme inducers, such as CBZ, phenytoin (PHT), and phenobarbital (PB).…”
Section: Introductionmentioning
confidence: 99%